2021
DOI: 10.1002/jsfa.11215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food matrix and probiotics on the bioavailability of curcumin in different nanoformulations

Abstract: BACKGROUND: Nanoparticles can improve the bioavailability of bioactive compounds. Concomitant intake of food can affect pharmacokinetic profiles by altering dissolution, absorption, metabolism, and elimination behavior. Studies on the effects of food and its supplements on the bioavailability of bioactives in nanoformulations are few. In this study, the effects of typical food (milk, sugar, high-fat diet, and regular kibble) and a widely consumed probiotic [Bifidobacterium lactis Bb-12® (Bb-12)] on the bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…There have been multiple reviews and research articles reported in the literature to increase the bioavailability of curcuminoids using various formulations [ 1 , 24 , 25 , 26 , 27 , 28 ]. Maheshwari, in 2010, reported higher solubility of lipophilic curcuminoids in traditional vehicles such as milk, clarified butter, and corn oil, as shown in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been multiple reviews and research articles reported in the literature to increase the bioavailability of curcuminoids using various formulations [ 1 , 24 , 25 , 26 , 27 , 28 ]. Maheshwari, in 2010, reported higher solubility of lipophilic curcuminoids in traditional vehicles such as milk, clarified butter, and corn oil, as shown in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the same study also showed a greater permeation of curcuminoids through the intestinal membrane using the non-everted rat intestinal sac model [ 24 ]. In a recent study by Han and coworkers, the authors showed that curcumin bioavailability has been improved using different kinds of nano-formulations [ 25 ]. For instance, fasting was the best method for the absorption of curcumin in nano-emulsions (Cur-NE) form, and sugar significantly enhanced the bioavailability of curcumin in single-walled carbon nanotubes (Cur-SWNT).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible to achieve a higher bioavailability of nutraceuticals by supplementing specific probiotics. Conversely, co‐ingestion of curcumin‐loaded nanoemulsions with B. lactis strain Bb‐12 contributed to colonization of the colon of the mice with this probiotic strain, but significantly inhibited curcumin absorption and reduced its bioavailability (Han et al., 2021). Hence, the relationship between intestinal microbiota composition and nutraceutical bioavailability deserves more extensive research.…”
Section: Current Strategies For Improving Bioavailability Of Nutraceu...mentioning
confidence: 99%
“…[19][20][21][22] To overcome these problems, various approaches, such as microcapsules, nanocapsules, emulsions, liposomes and micelles, have been employed for encapsulating curcumin to increase stability and to preserve health-promoting properties. [23][24][25][26][27][28][29][30] Micelles are promising hydrophobic bioactive compounds carriers that have attracted increasing interest in food and pharmaceutical applications. Micelles are self-organized in aqueous solution, consisting of amphiphilic molecules with solvophilic and solvophobic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the application of curcumin is usually limited by its poor water solubility, low absorption, rapid metabolism and instability 19‐22 . To overcome these problems, various approaches, such as microcapsules, nanocapsules, emulsions, liposomes and micelles, have been employed for encapsulating curcumin to increase stability and to preserve health‐promoting properties 23‐30 …”
Section: Introductionmentioning
confidence: 99%